2017
DOI: 10.5811/westjem.2016.10.31294
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Documentation in the Electronic Medical Record: Patterns of Use and Barriers

Abstract: IntroductionElectronic health records (EHR) have become ubiquitous in emergency departments. Medical students rotating on emergency medicine (EM) clerkships at these sites have constant exposure to EHRs as they learn essential skills. The Association of American Medical Colleges (AAMC), the Liaison Committee on Medical Education (LCME), and the Alliance for Clinical Education (ACE) have determined that documentation of the patient encounter in the medical record is an essential skill that all medical students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 6 publications
1
21
0
4
Order By: Relevance
“…Three of these studies with an experimental design were highlighted . There was a decline in the number of observational studies (35/75; 47%), compared to 2015 (36/61; 59%), but an increase in the number of studies using survey methodology (19/75; 25%) in 2016 compared to 10 of 61, 16% in 2015, and 0% in 2014. It should be noted that all survey studies in this review drew data from participants from multiple institutions per the predetermined selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these studies with an experimental design were highlighted . There was a decline in the number of observational studies (35/75; 47%), compared to 2015 (36/61; 59%), but an increase in the number of studies using survey methodology (19/75; 25%) in 2016 compared to 10 of 61, 16% in 2015, and 0% in 2014. It should be noted that all survey studies in this review drew data from participants from multiple institutions per the predetermined selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A US survey reported that 63% of emergency medicine clerkships allowed student documentation in the EMR (Box 1). One British medical school reported that 70% of their teaching practices allowed students to use an EMR . A Colombian study reported the need for clearer policies on students’ use of EMRs .…”
Section: Introductionmentioning
confidence: 99%
“…In some clinical environments such as emergency medicine, it is ideal for students to practice with real EHRs (Wittels, Wallenstein, Patwari, & Patel, 2017), but this is not always possible due to policies and regulations such as HIPAA in place. Hence, many medical students do not have access to EHRs in the clinical environment.…”
Section: Ehr In Educationmentioning
confidence: 99%